Seizures in E200K familial and sporadic Creutzfeldt‐Jakob disease. (16th October 2014) - Appel, S.; Chapman, J.; Cohen, O. S.; Rosenmann, H.; Nitsan, Z.; Blatt, I.
<x xml:space="preserve">Abstract</x> Background Although seizures (other than myoclonus) are frequently reported in Creutzfeldt‐Jakob disease (CJD), their frequency, clinical manifestations, and effect on the disease course is unknown. Objectives To characterize the frequency of seizures in E200K familial and sporadic CJD, to describe its semiology, EEG and MRI findings. Methods In this retrospective study, we reviewed all patients with CJD who were seen in the Sheba Medical Center between the years 2003–2012 and underwent clinical evaluation, genetic testing, EEG and MRI studies. The diagnosis of seizures was carried out based on documentation of episodes consistent with seizures or episode of unresponsiveness correlated with ictal activity in EEG. Results Sixty‐four probable patients with CJD were included in the study, 57 (89%) with E200K familial (fCJD) and 7 (11%) with sporadic (sCJD). Seizures occurred in 8 patients: 3 of 7 (43%) in patients with sCJD compared to 5/57 (9%) in patients with E200K fCJD (P = 0.04, chi‐square test). Two of E200K fCJD patients with seizures had other non‐prion etiologies for seizures (brain metastasis, known history of temporal lobe epilepsy which started 44 years before the diagnosis of CJD). Seizures occurred late in the course of the disease with an average of 12 days between the onset of seizures and death. Conclusion Seizures in E200K fCJD were infrequent and occurred late in the disease course. This difference suggests that E200K fCJD represents a separate subtype of the disease with distinct clinical characteristics.